2D Nanomaterials: Materials‐Informatics‐Assisted High‐Yield Synthesis of 2D Nanomaterials through Exfoliation (Adv. Theory Simul. 4/2019). Issue 4 (4th April 2019) - Nakada, Gentoku; Igarashi, Yasuhiko; Imai, Hiroaki; Oaki, Yuya
Abstract : A high‐yield synthesis of 2D nanomaterials through exfoliation is achieved using sparse modeling, as reported by Yuya Oaki and co‐workers in article number1800180 . Layered composites of inorganic layers and organic interlayer guests are exfoliated into nanosheets in organic media. Materials informatics combined with experiments, calculations, and data facilitates exploration of high‐yield exfoliation conditions in a minimum number of experiments with aid of experience and intuition.